PENERAPAN MODIFIKASI PERMAINAN TERHADAP HASIL BELAJAR SISWA SMP MUHAMMADIYAH 6 PADANG PADA MATERI KEBUGARAN JASMANI - Gracia; Syampurma , Hilmainur; Oktavani , Lucy; Zalindro, Ade (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low learning outcomes of students in physical fitness material, due to the teacher not having implemented game modification methods, which resulted in students being less active, quickly bored, and failing to achieve the Minimum Competency Assessment. The aim of this research is to improve the physical fitness learning outcomes of students in class VIII.1 at SMP Muhammadiyah 6 Padang. This study employed Classroom Action Research with 32 students as subjects, conducted over two cycles, each consisting of planning, action, observation, and reflection stages. Data collection techniques used modified physical fitness tests and assessments, while data analysis was carried out qualitatively and descriptively based on observation sheets and reflections. The results showed an increase in the average learning outcomes from 74.16 in cycle I to 84.88 in cycle II. In conclusion, the application of the game modification method proved effective in improving the physical fitness learning outcomes of students in class VIII.1 at SMP Muhammadiyah 6 Padang, and is therefore recommended as an innovative learning alternative for physical education teachers